2007
DOI: 10.1111/j.1365-2133.2007.08338.x
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient management of psoriasis: a multicentre service review to establish national admission standards

Abstract: Disease severity on admission for patients with psoriasis is greater in tertiary referral centres for psoriasis and is directly associated with length of stay. Length of stay should be used in conjunction with clinical measures such as PASI improvement to set national standards for quality in secondary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…19 A British multicenter study observed that increased Psoriasis Area Severity Index score was associated with increased hospital LOS. 20 Taken together with the results of the current study, it appears that Asian Americas have poor outpatient use for dermatologic disease, which in turn may predispose to poorer outcomes, increased rates of hospitalization, and increased LOS. Future research is needed to address whether disparities in hospitalization, cost, and LOS occur in Asian patients with other dermatologic disorders.…”
Section: Discussionmentioning
confidence: 72%
“…19 A British multicenter study observed that increased Psoriasis Area Severity Index score was associated with increased hospital LOS. 20 Taken together with the results of the current study, it appears that Asian Americas have poor outpatient use for dermatologic disease, which in turn may predispose to poorer outcomes, increased rates of hospitalization, and increased LOS. Future research is needed to address whether disparities in hospitalization, cost, and LOS occur in Asian patients with other dermatologic disorders.…”
Section: Discussionmentioning
confidence: 72%
“…[24] In a tertiary care center most of the times people with high grade disease get admitted for the in-patient care. [25] Over 60% of the patients stayed in the hospital for more than 10 days and among them nearly 22% stayed for more than a month. The average length of stay was nearly 18 days.…”
Section: Discussionmentioning
confidence: 99%
“…Dear Editor , The National Institute for Health and Care Excellence (NICE) identified treatment of moderate‐to‐severe psoriasis as an area for research . No recent studies have assessed treatment patterns and outcomes among patients hospitalized for psoriasis in the U.K …”
Section: Demographic and Clinical Characteristics Of The Patient Popumentioning
confidence: 99%